ANALYSIS OF FINANCIAL INDEPENDENCE RATIO IN MAMUJU REGENCY : ANALISIS RASIO KEMANDIRIAN KEUANGAN DI KABUPATEN MAMUJU (Lembaga Pengembangan Kinerja Dosen, 2022)
The local autonomy policy has given very broad authority to regulate local government. To implement local government, adequate finance is required. This research aims to analyze the financial independence ratio of the Mamuju Regency Government for the 2015-2019 Fiscal Year. To find out the level of local independence ratio is to compare the local revenue with financial assistance provided by the central government, provincial governments, and loans. The research method used is qualitative research with an inductive approach. Data collection techniques are carried out through interviews and documentation. Interviews were conducted to 5 (five) informants using snowball sampling technique. The data that has been collected is then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that the ratio analysis of local financial independence was 7.18% in the Very Low category. As for the inhibiting factors for the low ratio of financial independence, namely the lack of planning, the lack of use of technology, and the low competence of employees. With regard to these conditions, local governments should increase local revenue by optimizing local tax and levy revenues by making special applications to facilitate the collection of local taxes and levies, as well as innovating related to the development of Local Owned Enterprises in accordance with local potential.